2021
DOI: 10.3390/diagnostics11040690
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Immunohistochemistry of Soft Tissue and Bone Tumors: An Update on Biomarkers That Correlate with Molecular Alterations

Abstract: The diagnosis of benign and malignant soft tissue and bone neoplasms is a challenging area of surgical pathology, due to the large number, rarity, and histologic diversity of tumor types. In recent years, diagnosis and classification has been aided substantially by our growing understanding of recurrent molecular alterations in these neoplasms. Concurrently, the role of diagnostic immunohistochemistry has also expanded, with the development of numerous biomarkers based on underlying molecular events. Such biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 104 publications
0
15
0
Order By: Relevance
“…Several studies demonstrated that the loss of SMARCA4 was associated with a high risk of undifferentiated cancer, implying its anti-cancerous role[ 23 - 26 ]. Other studies detected the overexpression of SMARCA4 in various other types of cancer, including HCC[ 18 , 27 - 29 ], small cell lung cancer[ 10 , 11 , 30 - 32 ], acute leukemia[ 3 , 33 - 36 ] and neuroblastoma[ 37 , 38 ], thereby exemplifying its oncogenic role. In this study, we identified the overexpression of SMARCA4 Levels in 15 different types of cancer, excluding glioblastoma, kidney chromophobe, and kidney papillary cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that the loss of SMARCA4 was associated with a high risk of undifferentiated cancer, implying its anti-cancerous role[ 23 - 26 ]. Other studies detected the overexpression of SMARCA4 in various other types of cancer, including HCC[ 18 , 27 - 29 ], small cell lung cancer[ 10 , 11 , 30 - 32 ], acute leukemia[ 3 , 33 - 36 ] and neuroblastoma[ 37 , 38 ], thereby exemplifying its oncogenic role. In this study, we identified the overexpression of SMARCA4 Levels in 15 different types of cancer, excluding glioblastoma, kidney chromophobe, and kidney papillary cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…BSTS are heterogeneous tumors of mesenchymal origin with more than 100 histological subtypes [ 65 ], and each BSTS histotype presents a specific nucleic acid or protein profile, which allows molecular diagnosis of sarcoma [ 66 , 67 ].…”
Section: Clinical Utility Of Exosomes Detection In Liquid Biopsymentioning
confidence: 99%
“…8 Histologically, SS has a heterogeneous appearance and three histological variants have been described: monophasic, biphasic, and poorly differentiated. [9][10][11] Until a few years ago, a specific immunohistochemical (IHC) panel was not available and the diagnosis of SS relied on the detection of the t(X;18)(p11;q11) by molecular genetic or cytogenetic tests. 12 Both fluorescence in situ hybridization (FISH) and reverse transcription polymerase chain reaction (RT-PCR) analyses have been largely validated in the t(X;18)(p11;q11) detection, although cytogenetic evaluation is most widely used.…”
Section: Introductionmentioning
confidence: 99%